Perceived Barriers Affecting Extension Agents’ Personal Resilience Post-Hurricane - Amanda D. Ali; Angela Lindsey; Amy Harder; Lisa Lundy; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2020)
Related disaster stresses such as employee burnout negatively influences effective disaster response. The prevalence of hurricanes and other natural disasters impact Extension agents around the world. This research explored barriers affecting UF/IFAS Extension agents’ abilityto effectively engage in post-hurricane response. Resilience and burnout literature led to a researcher-developed conceptual model. A basic qualitative research design facilitated face-to-face and telephone interviews with UF/IFAS Extension agents engaged in hurricane-response efforts. Results showed mental and physical stress, performance deficits, and perceived lack of motivation negatively affected agents’ ability to engage in post-disaster response. Overall recommendations were to: (a) strengthen communication between Extension administration and county agents, (b) inform agents of ongoing disaster developments to clarify professional disaster expectations, and (c) provide trainings on mental health and coping strategies in disasters. Results of this research suggest this phenomenon should be examined in other Extension system
Keywords: barriers; Extension; hurricane; personal resilience; post-disaster response